1965
DOI: 10.1111/j.1744-7348.1965.tb01237.x
|View full text |Cite
|
Sign up to set email alerts
|

The suppression of ascospore production to facilitate the control of apple scab (Venturia inaequalis (Cke.) Wint.)

Abstract: SUMMARYUsing phenylmercuric chloride (PMC) as the experimental fungicide it has been shown that spraying trees once in autumn at 0.05% and again just before bud‐burst at 0.01% reduced scab infection on blossom truss leaves by over 99% in the following spring. In another orchard 0.01% PMC sprays in autumn and just before bud‐burst, followed by fungicide sprays in spring and early summer, gave complete control of scab. In a third orchard, which was subject to contamination by ascospores from non‐treated apple tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 4 publications
3
8
0
Order By: Relevance
“…Many factors can explain these dispersal distance differences, including orchard conditions and differences in wind direction and velocity (see [16]). In this study, we confirmed that dispersal of the greater part of V. inaequalis spores in orchards was intrinsically very restricted, which is in agreement with several other authors (e.g., [54-56]), who demonstrated that no scab lesion development was detected at 15 to 60 metres beyond an inoculum source. We do not dismiss the sporadic events of Long Distance Dispersal (LDD).…”
Section: Discussionsupporting
confidence: 93%
“…Many factors can explain these dispersal distance differences, including orchard conditions and differences in wind direction and velocity (see [16]). In this study, we confirmed that dispersal of the greater part of V. inaequalis spores in orchards was intrinsically very restricted, which is in agreement with several other authors (e.g., [54-56]), who demonstrated that no scab lesion development was detected at 15 to 60 metres beyond an inoculum source. We do not dismiss the sporadic events of Long Distance Dispersal (LDD).…”
Section: Discussionsupporting
confidence: 93%
“…Knowledge of dispersal distance and factors affecting ascospore spread is essential for disease management. Earlier studies showed that incidence of leaf and fruit scab was negligible 15–60 m from a point source of inoculum (Palmiter, 1946; Hirst and Stedman, 1962; Burchill and Hutton, 1965) and only a few airborne ascospores were trapped at a distance of 60 m (Hirst and Stedman, 1962). Moreover, one study demonstrated that the number of ascospores in the air was negligible 5.4 m from the source of inoculum (Kaplan, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Fifty leaf discs were placed in each of 10 metal mesh bags, inside a shade netting box (1 m×1 m×10 cm) during winter within 2 km from the trial orchard (as described in Schwabe et al 1989). Every 2 weeks a bag was taken out and ascospores were extracted, as previously described (Burchill and Hutton 1965). Ascospore maturity was evaluated by counting spore numbers once every 2 weeks under a stereomicroscope at 100× magnification.…”
Section: Monitoring Of Ascospore Maturationmentioning
confidence: 99%